1991
DOI: 10.1557/proc-235-179
|View full text |Cite
|
Sign up to set email alerts
|

C Implantation for Suppression of Dislocation Formation

Abstract: This paper will show that annealing of Si implanted with moderate doses of 725 keV B results in the formation of secondary defects, the so-called category I dislocations. Surprisingly, 12C, with roughly the same mass as 11B, behaves in a very different way. Carbon implant damage does not result in dislocation formation even for damage levels > 100 times higher than that required for B implants. C is also able to avoid dislocation formation of co-implanted B ions. The C-dose needed to avoid dislocation forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…11,12 This effect is studied here as a function of the overlap between the C profile and the damage created by a 150 keV Si implant ͑for which the damage distribution peaks at about 0.2 m͒ performed to a dose of 3ϫ10 14 cm Ϫ2 . The C was implanted in three such samples to a dose of 3ϫ10 15 cm Ϫ2 , each with a different energy: 700 keV ͑R p Ϸ1.2 m͒, 170 keV ͑R p Ϸ0.4 m͒, and 70 keV ͑R p Ϸ0.2 m͒.…”
Section: A Effect Of C On Dislocation Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 This effect is studied here as a function of the overlap between the C profile and the damage created by a 150 keV Si implant ͑for which the damage distribution peaks at about 0.2 m͒ performed to a dose of 3ϫ10 14 cm Ϫ2 . The C was implanted in three such samples to a dose of 3ϫ10 15 cm Ϫ2 , each with a different energy: 700 keV ͑R p Ϸ1.2 m͒, 170 keV ͑R p Ϸ0.4 m͒, and 70 keV ͑R p Ϸ0.2 m͒.…”
Section: A Effect Of C On Dislocation Formationmentioning
confidence: 99%
“…10 Moreover, dislocation formation is suppressed in B-and P-implanted Si if an additional C implantation is performed. 11,12 Some indications that the presence of C may reduce the transient diffusion of B have also been reported. 13 Also gettering of metallic impurities such as gold, 14 copper, 15 or iron 16 in C-implanted silicon has been observed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, it has been reported that C coimplantation can be used to reduce TED of B. 41,42 This reduction has been attributed [43][44][45] to the fact that the implanted C provides a sink for excess interstitials during annealing. The efficacy of C coimplantation in suppressing TED is limited by the fact that the C needs to getter its own interstitial damage in addition to the interstitials from the dopant implant.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of C coimplantation in suppressing TED is limited by the fact that the C needs to getter its own interstitial damage in addition to the interstitials from the dopant implant. 44 It could therefore be more efficient to incorporate substitutional C in c-Si before implanting the dopant species, which is an additional subject of research in this article.…”
Section: Introductionmentioning
confidence: 99%